Ratio Legis Fast Track Lagislation Dalam Pembentukan Perundang Undangan Di Indonesia - Ahmad Althof; Moh. Sumriyadi (Jurnal Hukum Lex Generalis, 2023)
This research examines and reconstructs the concept of fast track legislation in the mechanism for forming legislation in Indonesia. This has resulted in many pros and cons regarding the laws that have been issued and ratified by the DPR and the President. It is felt that the resulting law product does not comply with the philosophy of Law No. 12 of 2011 concerning the formation of statutory regulations. This is proven by several laws that have been produced that are not appropriate and have caused conflict in society, such as the Job Creation Law, the Constitutional Court Law, the Corruption Eradication Committee Law, the Covid-19 Law, and most recently the IKN Law. The research method used is using a normative juridical research type with data sources from literature, both journals and books and a number of applicable regulatory norms..